Design and Implementation of a Reconfigurable Test Environment for Network Measurement Tools Based on a Control and Management Framework - Fatih Abut; Mehmet Kızıldağ (Applied Sciences)
To be applicable to real-world networks, a realistic evaluation of network measurement tools requires the conditions of the test network to be as similar as possible to the networks in which they are later deployed. Thus, having an existing real-world network which can be utilized for testing, while also allowing the reconfiguration of certain characteristics and features, is of significant interest to researchers. Providing the researchers with corresponding management tools with which they can introduce artificial conditions and topology changes into the network would help in realizing more realistic testbed setups and scenarios. The purpose of this study is to develop a configurable test environment based on the Control and Management Framework (OMF) to support researchers in a realistic empirical evaluation of network measurement tools. The proposed OMF-enabled test environment has the merit of automatizing the deployments and executions of any measurement experiments, collecting their final estimates, and then transporting them back to a single experiment controller without requiring any physical access to the corresponding experimental nodes used. It is demonstrated how the test environment can be used for the evaluation of network measurement experiments based on four representative case studies. These include validating the accuracy of end-to-end round-trip time and available bandwidth estimation tools, measuring the TCP and UDP throughput, and analyzing the impact of packet loss and jitter on VoIP performance, all conducted over dynamically adjusted testbed configurations. These case studies highlight the versatility and effectiveness of the OMF-enabled test environment, positioning it as a valuable tool for advancing the realistic evaluation of network measurement tools in controlled yet adaptable settings.